Factors Influencing Adherence to ART: New Insights from a Center Providing Free ART under the National Program in Delhi, India. (May 2013) - Anuradha, S.; Joshi, Anant; Negi, Madhubala; Nischal, Neeraj; Rajeshwari, K.; Dewan, Richa
Background: Adherence to therapy is central to the success of antiretroviral treatment (ART). With the availability of free ART under the national program in India, cost of ART is no longer the primary determinant of adherence. This study evaluated the adherence and factors influencing it among patients receiving free ART in a public health ART center in India. Methods: The adherence and its influences among 250 HIV-positive patients on first line ART for at least 3 months from the ART Center of Maulana Azad Medical College and Lok Nayak Hospital, New Delhi, India were analyzed. The adherence was assessed by patients' self report using the adult AIDS Clinical Trial Group (ACTG) questionnaire and counter checked with pharmacy records. The association of various parameters affecting adherence levels was analyzed by using SPSS package and Epiinfo software. Results: Of the 250 patients, 242 (96.8%) had optimum adherence (>95%) and 8 (3.2%) were "non-adherent." CD4 counts ( P = 0.05), high level of belief among patients, patients' knowledge about importance of adherence ( P = 0.04), and sound mental health were positively influencing adherence. The main barriers to adherence were poor mental health and negative psychological states in the patients (0.001). The presence of adverse reactions to ART also resulted in poorer adherence. Conclusions: The modifiable factors most strongly associated with good adherence rates were higher current CD4 counts, patients' beliefs in ART, and positive mental health. These factors can be targeted by simple, practical interventions to improve and maintain high adherence levels.